Impact of Digital Marketing Development on Entrepreneurship in Kathmandu - Mahato, Ravi Kumar; Rawat, Ramesh (Nepalese Journal of Management, 2025)
This study examines the impact of digital marketing development on entrepreneurship in Kathmandu. Business growth is the dependent variable. The selected independent variables are social media marketing, email marketing, influencer marketing, participation in online advertising network, and usage of mobile app marketing. The primary sources of data is used to assess the opinions of respondents regarding social media marketing, email marketing, influencer marketing, participation in online advertising network, usage of mobile app marketing and business growth. The study is based on the primary data of 126 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and impact of digital marketing development on entrepreneurship in Kathmandu. The study showed a positive impact of social media marketing on business growth. It indicates that use of social media marketing leads to increase in business growth. Similarly, the study showed a positive impact of email marketing on business growth. It indicates that use of email marketing leads to increase in business growth. Likewise, the study showed a positive impact of influencer marketing on business growth. It indicates that effective influencer marketing mechanism leads to increase in business growth. Further, the study showed a positive impact of participation in online advertising network on business growth. It indicates that more participation in online advertising network, higher would be the business growth. Moreover, the study showed a positive impact of usage of mobile app marketing on business growth. It indicates that more usage of mobile app marketing leads to increase in business growth.